Optimizing The Role of Service Quality Towards Satisfaction Through Trust in BPJS Ketenagakerjaan Participants - Tri Alfian Safi'i (Universitas Mercu Buana, 2023)
This study aims to analyze the effect of service quality and trust on the satisfaction of workers who have participated in the BPJS for Employment Sidoarjo Branch Office, as well as analyze the mediating role of trust in the effect of service quality on satisfaction. This research is a causal research with a quantitative approach. Collecting research data using a questionnaire distributed to formal and informal workers who have become members of the BPJS for Employment Sidoarjo Branch Office social security. Sampling using purposive sampling. Data analysis technique using PLS SEM analysis. The results of the study explain that service quality and trust have a positive effect on participant satisfaction at the BPJS for Employment Sidoarjo Branch Office. The results of the study also explain that trust can mediate the effect of service quality on participant satisfaction at the BPJS for Employment Sidoarjo Branch Office. These results explain that the better the quality of service from the BPJS for Employment and the better the level of trust from workers who are program participants will be able to increase the satisfaction of workers who are participants in the social security program. In addition, improving the quality of services that are getting better from BPJS for Employment staff will be able to increase company confidence in the services provided and then lead to higher satisfaction with employment social security services provided by BPJS for Employment.